Design and Control of Underwater Robots with Rotating Thrusters - Ali Jebelli; M. C.E. Yagoub; B. S. Dhillon (IAES International Journal of Robotics and Automation (IJRA), 2016)
Among other robots, underwater robot design involves critical control issues due to complex non-linear force and turns controlling. In this paper, a robust approach was proposed to efficiently control the behavior of an underwater robot through five degrees of freedom. Also, by designing a new type of a pair of thruster with the ability to 360 degree rotation along with a mass shifter, it gives this possibility to the robot that easily and with a minimal energy, change its depth quickly, preserving its balance best possible at the same time.